2015
DOI: 10.1007/s00464-015-4550-x
|View full text |Cite
|
Sign up to set email alerts
|

Intraluminal lavage to remove exfoliated tumor cells after colorectal endoscopic submucosal dissection

Abstract: Tumor cells are exfoliated into the intestinal lumen by tumor manipulation during colorectal ESD. There seems to be a risk for implantation after ESD, as well as rectal surgery. Sufficient intraluminal lavage of more than 1000 ml may be desirable to remove exfoliated tumor cells after colorectal ESD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 15 publications
0
15
0
1
Order By: Relevance
“…4 Previous studies have shown that tumor cells exfoliate from CRC into the intestinal lumen, especially when the tumor is manipulated. 5,6 Yet, the risk of spontaneous tumor seeding, that is, implantation of tumor cells in damaged mucosa when polypectomy or biopsy is performed in the presence of CRC elsewhere in the colorectum, is estimated to be low. 7 However, the possibility of mechanical tumor seeding during colonoscopy, involving iatrogenic implantation of tumor cells in damaged mucosa, has never been explored.…”
Section: Background and Aimsmentioning
confidence: 99%
“…4 Previous studies have shown that tumor cells exfoliate from CRC into the intestinal lumen, especially when the tumor is manipulated. 5,6 Yet, the risk of spontaneous tumor seeding, that is, implantation of tumor cells in damaged mucosa when polypectomy or biopsy is performed in the presence of CRC elsewhere in the colorectum, is estimated to be low. 7 However, the possibility of mechanical tumor seeding during colonoscopy, involving iatrogenic implantation of tumor cells in damaged mucosa, has never been explored.…”
Section: Background and Aimsmentioning
confidence: 99%
“…It has been reported that tumor cells are exfoliated into the intestinal lumen during ESD 7 . After submucosal dissection, the ulcer bed is exposed to these exfoliated tumor cells for a long time during ESD, which can lead to TCI.…”
Section: Discussionmentioning
confidence: 99%
“…Intraluminal lavage with > 1000 mL fluid after ESD reportedly is useful for removing exfoliated tumor cells after colorectal ESD 7 . Use of this method may contribute to preventing TCI after ESD.…”
Section: Discussionmentioning
confidence: 99%
“…According to a meta-analysis, intraoperative rectal washout can reduce local recurrence after rectal cancer surgery [ 11 ]. Moreover, a recent study revealed that tumor cells can be exfoliated into the intestinal lumen during colorectal ESD [ 12 ], although little is known about the clinical significance of exfoliated tumor cells related to endoscopic procedures. Interestingly, a case report suggested that colorectal adenocarcinoma cells might be implanted into the artificial ulcer after endoscopic resection [ 13 ].…”
Section: Discussionmentioning
confidence: 99%